Subject to natural law: a meditation on the 'two cultures' problem. [Paper in: Thematic articles: Science. Kirby, Vicki (ed.).] - Kirby, Vicki (Australian feminist studies, 2008)
In the context of feminist studies, argues that the gulf between the humanities and the sciences now seems wider than ever. As the humanities have found ways to subject scientific research to textual and cultural analysis, there has been a tendency towards diagnostic fault-finding, suspicion and accusation that militates against more generous styles of engagement. Indeed, the urgent need to interrogate the motivations and premises of scientific practice - the self-evidence of objective truth and the juggernaut of instrumental progress - has fostered a sense of political purpose whose own truth claims and progressivism escape similar scrutiny. Explores this awkward impasse by reinvigorating its terms of reference. (Quotes from original text)